Lumbo-pelvic biomechanics and quadratus lumborum asymmetry in cricket fast bowlers - Crewe, H.; Campbell, Amity; Elliott, B.; Alderson, J. (Sports Medicine Australia, Elsevier Australia, 2012)
PURPOSE: This study aimed to analyse lumbo-pelvic lateral flexion kinematics and kinetics in junior fast bowlers and compare bowlers with varying quadratus lumborum (QL) cross sectional area (CSA) asymmetry profiles. METHODS: Magnetic resonance imaging was used to determine QL CSA of 39 participants who also underwent three-dimensional analysis of their bowling action. RESULTS: Bowlers with greater than 10% QL asymmetry (N = 26) experienced a larger peak lumbo-pelvic lateral flexion; angle (21.6° ± 4.2), angular velocity (314.9°.s ± 86.6), moment (12.8 Nm.kg.m ± 2.5), positive power (25.6 W.kg.m ± 12.6) and negative power (48.6 W.kg.m ± 20.9) compared with the bowlers with less than 10% asymmetry (N = 13) (angle 18.1° ± 1.9, angular velocity 243.8°.s ± 64.9, moment 10.4 Nm.kg.m ± 2.8, positive power 14.7 W.kg.m ± 7.4, and negative power 33.8 W.kg.m ± 17.7), (p<0.05). CONCLUSION: Fast bowlers with QL CSA asymmetry in excess of 10% experience increased lumbo-pelvic lateral flexion loads during bowling. As increased lateral flexion loads may increase the risk of spondylolysis development, the presence of large QL asymmetry may be a useful screening tool for identifying bowlers at risk of developing lumbar spondylolysis.